The productiveness of Bootstrap simulator in evaluating the accuracy parameters of measurement system for ball screw - Chuan, Zun Liang; Muhamad Husnain, Mohd Noh; Mohd Akramin, Mohd Romlay; Mu, Wen Chuan (IOP Publishing, 2019)
Ball screw is an essential mechanical component of computer numerical controlled (CNC) milling machine, which the positioning accuracy of ball screw is highly associated with lead angle accuracy and axial clearance. In particular, the inaccuracy of lead angle and axial clearance of ball screw can be massively affected the inaccuracy of positioning, leading to the degraded quality of manufactured products. Therefore, a reliable and productive measurement system analysis is indeed in monitoring the accuracy parameters of the ball screw. The main objective of this study is to propose using the Bootstrap simulator in monitoring the accuracy parameters of measurement system for ball screw, with the abstraction of cost and time. The accuracy parameters of the measurement system are including stability, bias and linearity. Based on the simulation results, it can be concluded that the Bootstrap simulator is more productive in monitoring the accuracy parameters of measurement system for ball screw compared to the Monte Carlo simulator. This is due to the Bootstrap simulator can be yielded a lower uncertainty of simulation compared to the Monte Carlo simulator. Furthermore, the Bootstrap simulator is also more advantages compared to the Monte Carlo simulator as this simulator can be carried out with small sample size of measurement data.